Plasmodium cysteine repeat modular proteins 1-4: complex proteins with roles throughout the malaria parasite life cycle. - Thompson, J; Fernandez-Reyes, D; Sharling, L; Moore, S; Eling, WM; Kyes, SA; Newbold, C; Kafatos, F; Janse, C; Waters, A (2007)
The Cysteine Repeat Modular Proteins (PCRMP1-4) of Plasmodium, are encoded by a small gene family that is conserved in malaria and other Apicomplexan parasites. They are very large, predicted surface proteins with multipass transmembrane domains containing motifs that are conserved within families of cysteine-rich, predicted surface proteins in a range of unicellular eukaryotes, and a unique combination of protein-binding motifs, including a >100 kDa cysteine-rich modular region, an epidermal growth factor-like domain and a Kringle domain. PCRMP1 and 2 are expressed in life cycle stages in both the mosquito and vertebrate. They colocalize with PfEMP1 (P. falciparum Erythrocyte Membrane Antigen-1) during its export from P. falciparum blood-stage parasites and are exposed on the surface of haemolymph- and salivary gland-sporozoites in the mosquito, consistent with a role in host tissue targeting and invasion. Gene disruption of pcrmp1 and 2 in the rodent malaria model, P. berghei, demonstrated that both are essential for transmission of the parasite from the mosquito to the mouse and has established their discrete and important roles in sporozoite targeting to the mosquito salivary gland. The unprecedented expression pattern and structural features of the PCRMPs thus suggest a variety of roles mediating host-parasite interactions throughout the parasite life cycle.